2020
DOI: 10.1111/jppi.12333
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Logic Model for the Triple‐C Intervention: A Practice‐Derived Intervention to Support People with Intellectual Disability and Challenging Behavior

Abstract: Partly due to a lack of evidence-based methods to support people with intellectual disability (ID) and challenging behavior, their needs are often poorly met. One way to generate rapid evidence is to systematically describe and monitor interventions that are considered to be "good practice"-to develop evidence based on practical knowledge. This study describes the Dutch practice-based intervention Triple-C (Client, Coach, Competence). The intervention was developed in practice to support people with severe ID … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 37 publications
(48 reference statements)
0
19
0
1
Order By: Relevance
“…This study has value for researchers and practitioners, as the ecological perspective provides insight into recent studies on implementing and maintaining active support in various services, which have concluded that hands-on training and managerial leadership seem to be crucial organizational aspects (Beadle-Brown, Bigby, & Bould, 2015;Bigby & Beadle-Brown, 2018;Bigby, Bould, Iacono, Kavanagh, & Beadle-Brown, 2019;Deveau & McGill, 2016a, 2016b. As Bould, Beadle-Brown, Bigby, and Iacono (2016) (Deveau and McGill, 2019;Deveau, Gore, & McGill, 2020;Olivier-Pijpers, et al, 2018;Schippers, 2019;Tournier et al, 2020;Walker, 2012). During organizational changes, continuous discussions on aligning staff attitudes with the organizational vision, staff training in positive attitudes and reduced restraint use, and sufficient information about residents' needs to enhance resident-staff bonding are also necessary (Olivier-Pijpers, Cramm, & Nieboer, 2019;Philips & Rose, 2010;Walker, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…This study has value for researchers and practitioners, as the ecological perspective provides insight into recent studies on implementing and maintaining active support in various services, which have concluded that hands-on training and managerial leadership seem to be crucial organizational aspects (Beadle-Brown, Bigby, & Bould, 2015;Bigby & Beadle-Brown, 2018;Bigby, Bould, Iacono, Kavanagh, & Beadle-Brown, 2019;Deveau & McGill, 2016a, 2016b. As Bould, Beadle-Brown, Bigby, and Iacono (2016) (Deveau and McGill, 2019;Deveau, Gore, & McGill, 2020;Olivier-Pijpers, et al, 2018;Schippers, 2019;Tournier et al, 2020;Walker, 2012). During organizational changes, continuous discussions on aligning staff attitudes with the organizational vision, staff training in positive attitudes and reduced restraint use, and sufficient information about residents' needs to enhance resident-staff bonding are also necessary (Olivier-Pijpers, Cramm, & Nieboer, 2019;Philips & Rose, 2010;Walker, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…This created a “messy” situation that negatively impacted management of challenging behaviour. Research indicates support from managers and psychologists through practice leadership, with frequent formal and informal staff contact, is vital for improving management of challenging behaviours and building a coherent team culture, leading to staff receiving and sharing guidance on how to provide support in line with residents’ behaviours (Deveau & McGill, 2019; Deveau, Gore, & McGill, 2020; Olivier‐Pijpers, et al, 2018; Olivier‐Pijpers et al, 2019; Tournier, Hendriks, Jahoda, Hastings, & Embregts, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations